Evidence of kinetic arrest in Se doped CoS2. (October 2016) - Mishra, Saroj Kumar; Rawat, R.
Abstract: Our systematic path dependent resistivity study in H – T space shows that paramagnetic (PM)–ferromagnetic (FM) transition in CoS 1.76 Se 0.24 is kinetically arrested. The resistivity at low temperature depends on the path followed in H – T space and the critical field required for PM to FM transition varies non-monotonically with temperature. Measurements under CHUF (cooling and heating in unequal magnetic field) protocol show reentrant transition on warming under higher magnetic field (than that applied during cooling), which indicate that PM state is the non-equilibrium state. Among the growing list of diverse system showing glass like arrested magnetic states, the present system is the first example where, kinetic arrest is observed for a disordered (here PM) to ordered (here FM) magnetic transition. Abstract : Highlights: First report on kinetic arrest of disorder-order magnetic transition. Re-entrant transition on warming i.e. PM to FM to PM transition in CoS1.76 Se0.24 . Resistivity at low temperature depends on the path followed in H – T space. Critical field required for PM to FM transition varies non-monotonically. Open loop in MR decreases with increase in temperature.